2009
DOI: 10.1007/s10943-009-9267-5
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Religiosity, Sexual Education, and Parental Factors with Risky Sexual Behaviors Among Adolescents and Young Adults

Abstract: Abstract:This study examined the association of religiosity, sexual education and family structure with risky sexual behaviors among adolescents and young adults. The nationally representative sample, from the 2002 National Survey of Family Growth, included 3,168 women and men ages 15-21 years. Those who viewed religion as very important, had frequent church attendance, and held religious sexual attitudes were 27-54% less likely to have had sex and had significantly fewer sex partners than peers. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
66
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 40 publications
10
66
0
11
Order By: Relevance
“…This finding is supported by earlier research showing that adolescents from two-parent families were less likely to have sex and had fewer sexual partners (Price & Hyde, 2009;Haglund & Ferring, 2010). Similar findings from a Greek study showed that adolescents with an unstable home environment, due to divorce, recent death, or not living with their mother, were more likely to be sexually active (Tsitsika et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is supported by earlier research showing that adolescents from two-parent families were less likely to have sex and had fewer sexual partners (Price & Hyde, 2009;Haglund & Ferring, 2010). Similar findings from a Greek study showed that adolescents with an unstable home environment, due to divorce, recent death, or not living with their mother, were more likely to be sexually active (Tsitsika et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Algumas bases de dados destacam-se pela grande quantidade de artigos publicados utilizando seus dados, como a National Survey of Family Growth (NFSG) (BILLY et al, 1994;COOKSEY et al, 1996;BREWSTER et al, 1998;MANLOVE et al, 2006;HAGLUND;FEHRING, 2010), a National Longitudinal Study of Adolescent Health (Add Health) (BEARMAN; BRÜCKNER, 2001;MEIER, 2003;ROSTOSKY et al, 2003;SMITH, 2005;FRANCIS, 2007;MENNING et al, 2007) e as DHS − Demographic Health Surveys (GUPTA, 2000;ADDAI, 2000;LONGO, 2001;ISHIDA;STUPP;McDONALD, 2011), que, embora sejam mais limitadas em termos de informação sobre religião, têm boa amostragem e intervalos decenais.…”
Section: Descrição Dos Textos Encontrados Na Rbsunclassified
“…Previous studies support the finding that attendance to religious services not only leads to increased adherence to religious teachings of avoiding risky sex behaviors but also exposes them to social support from peers who have similar practices and beliefs. The group norms, such as religious teachings that support rejection of risky behaviors, influence the individual to do the same (Haglund & Fehring, 2009;Landor et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggest that religion, religiosity, and open parent-sex communication promote safe sex behaviors among youths (Delgado-Infante & Ofreneo, 2014;Freedman-Doan, Fortunato, Henshaw, & Titus, 2013;Gipson, Gultiano, Avila, & Hindin, 2012;Haglund & Fehring, 2009;Hutchinson, 2007;Landor, Simons, Simons, Brody, & Gibbons, 2011). Family and religion are the two most important social systems in the Filipino culture (Alampay & Jocson, 2011;Chen, Thompson, & Morrison-Beedy, 2010;Nadal, 2009).…”
mentioning
confidence: 99%